Propuesta de un programa de prevención de riesgos laborales en las actividades de la Modalidad de Agropecuaria del Colegio Técnico Profesional de Pococí (CTPP) - Mora-Ortega, Alejandra (Instituto Tecnológico de Costa Rica, 2017)
The Professional Technical High School of Pococí has a population of 205 teachers, 36 administratives and a total of 1922 students enrolled; of which 24 teachers and 224 students correspond to the Agricultural Modality, whose specialties to opt for the title of Technical are Agroecology, Agroindustry, Irrigation and Drainage and Agropecuaria in agricultural production. In the institution there is a Risk Management Plan stipulated by the Ministry of Public Education; but this is framed in the attention of emergencies and not in the prevention of occupational risks. Currently there are no records of accidents, incidents nor are the risks to which teachers and students are exposed in their teaching and learning tasks; It is for this reason that the general objective of the project is to carry out a program of prevention of occupational risks in the activities of the Modality of Agriculture. At the diagnostic stage, tools were used to identify the hazards or deficiencies in the different activities, including checklists of working conditions, planned observations to see how the different activities are carried out and the risks to which they are exposed. With the level of risk established by the Guide for the identification of hazards and the evaluation of occupational health and safety risks, INTE 06-31-07: 2011, the program for the prevention of occupational hazards was developed in the activities of the Modality of Agriculture of the Professional Technical High School of Pococí, where the necessary operational controls for the different risks are determined. For Level I risks, procedures were designed and Level II and III risks were identified in a list of necessary controls. In addition, it is recommended the approval of the Occupational Health Policy, the formation of the Occupational Health Commission and the hiring of a professional in Occupational Health who give the training and advice necessary for the implementation of the prevention program.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2017.
Keywords: Riesgos laborales; Prevención de riesgos; Colegio técnico; Peligros; Seguridad ocupacional